Structural Characteristics and Electrical Conductivity of Spark Plasma Sintered Ytterbia Co‐doped Scandia Stabilized Zirconia. Issue 1 (6th October 2016) - Shukla, Vandana; Kumar, Ashutosh; Labbaveettil Basheer, Ishamol; Balani, Kantesh; Subramaniam, Anandh; Omar, Shobit
Abstract : The effect of replacing Sc2 O3 with Yb2 O3 on the structural and electrical properties of x Yb2 O3 –(12– x )Sc2 O3 –88ZrO2 has been investigated. Spark plasma sintering technique is employed to fabricate dense bulk samples from the nano‐sized powders. X‐ray diffraction and transmission electron microscopy performed on pellets indicate the existence of cubic and rhombohedral phases in 12ScSZ, and a single cubic phase in all the co‐doped compositions. However, Raman spectroscopic studies suggest the presence of a metastable tetragonal t ″‐phase along with rhombohedral phases in 12ScSZ, whereas a single cubic phase in all the co‐doped compositions. Significant enhancement in the conductivity of grain and grain boundary is observed on replacing Sc2 O3 with Yb2 O3 . In the intermediate temperature range, 1Yb11ScSZ exhibits the highest, while 12ScSZ shows the lowest conductivity values, which is attributed to corresponding phases present in that range. Through co‐doping with >1 mol% Yb2 O3 leads to conductivity decrease, but the value remains higher than that of 12ScSZ. A sharp conductivity change is observed in 12ScSZ and 1Yb11ScSZ samples, which is attributed to partial phase transition as well to the formation of cation‐vacancy complexes. In this work, the beneficial effect of Yb2 O3 co‐doping in 12ScSZ on the phase and conductivity has been highlighted.